Current state and restoration of sea trout and Atlantic salmon populations in three river systems in the eastern Gulf of Finland - Peuhkuri, Nina; Saura, Ari; Koljonen, Marja-Liisa; Titov, Sergey; Gross, Riho; Kannel, Risto; Koskiniemi, Jarmo
Sout-East Finland - Russia ENPI CBC 2007-2012 Contact person: Nina Peuhkuri We investigated by electrofishing the state of sea trout population and also the fish assemblage as a whole in two Finnish–Russian cross-border river systems, Mustajoki/Tchornaja/Soskuanjoki/Malinovka and Hounijoki/Buslovka/Rakkolanjoki/Seleznevka, draining into the Gulf of Finland. Based on the fish assemblage, we assessed the ecological status of the rivers. In the third of our target river systems, Gladyshevka/Rotshinka in the Karelian Isthmus, our interest was particularly focused on the Atlantic salmon population. In Mustajoki/Tchornaja/Soskuanjoki/Malinovka, trout dominated in density the upper reaches and small tributaries, their densities decreasing towards the river mouth. Restoration of rapids led to increased trout densities, but benign weather conditions may partly explain the trend. The trout population in this river system was found to be genetically unique and diverse. In Hounijoki/Buslovka/Rakkolanjoki/Seleznevka, only a few trout were found − from the Russian side. The absence of trout, especially from the upper reaches, is due to migration obstacles but also probably to poorer water quality compared to Mustajoki/Tchornaja/Soskuanjoki/Malinovka. This was also reflected in the poorer ecological status. In Gladyshevka/Rotshinka, both salmon and trout were caught from the River Gladyshevka, but neither of these from the River Rotshinka. The densities of salmon in the River Gladyshevka partly reflect the releases of hatchery fish. We established a broodstock of the Mustajoki/Tchornaja/Soskuanjoki/Malinovka trout to enhance restoration of this native sea trout population still found on both the Finnish and Russian sides of the cross-border riversdraining into the Gulf of Finland. We also transferred wild-caught trout to the River Soskuanjoki on the Finnish side and upper reaches of the River Malinovka on the Russian side to promote the existence of the population in the whole river system in the wild. Later observations of ...